The Transmission of Fundamentalist Ideology in the Method of Legal Ijtihad: A Study of Ahmad Hassan's Interpretation of the Qur'an in the Book al-Furqon - Abd Muhaimin; Indal Abror (QOF, 2023)
This article is the result of a literature review on the book "al-Furqan" by Ahmad Hassan, focusing on how fundamentalist ideologies are transmitted through the method of legal ijtihad in his interpretation. The research explores two main aspects: first, how A. Hassan's fundamentalist ideology is transmitted through the method of legal ijtihad, and second, how A. Hassan's interpretation practices of legal verses are presented in the book. Using a qualitative method, the researcher collected and analyzed the book "al-Furqan" as the primary data source. Additionally, a review of related books, scholarly articles, and other literature was conducted as secondary data sources. The research findings indicate that A. Hassan, while leaning towards textual interpretation, does not deny contextual approaches in some cases, particularly concerning Islamic law. It is noteworthy that his arguments are often based on opinions from various legal schools (mazhab). He also integrates various approaches according to the context of Islamic law, demonstrating the dynamic and adaptive nature of his ijtihad. The legal ijtihad method developed by Hassan offers a flexible framework rooted in fundamental Islamic principles, allowing its application in various contexts and situations. The study provides insights into how A. Hassan's interpretative approach can enhance understanding of religious texts and their application in modern contexts, showcasing the diversity and richness of thought within the Islamic intellectual tradition.